1987
DOI: 10.1002/chin.198709159
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Syntheses and Analgesic/Antiinflammatory Activities of Novel 2‐(5‐Aroyl‐pyrrolo)alkanoic Acids.

Abstract: Reaction of the cyanopyridine (I) with the pyrrole (II) under Houben‐Hoesch conditions gives the ketone (III), which is converted to the nicotinyl derivative (IVa); a similar procedure leads to the picolinyl derivative (IVb).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The fluoro-substituted benzyl cyanide leads to ketone 16 (eq 1). Although benzylic fluoro-substituents are known to form carbocations in superacid, 3a there is no evidence for such chemistry in this system. The dinitrile ( 17 ) provides the 1,6-diketone from reaction with benzene in superacid (eq 2).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The fluoro-substituted benzyl cyanide leads to ketone 16 (eq 1). Although benzylic fluoro-substituents are known to form carbocations in superacid, 3a there is no evidence for such chemistry in this system. The dinitrile ( 17 ) provides the 1,6-diketone from reaction with benzene in superacid (eq 2).…”
Section: Resultsmentioning
confidence: 86%
“…1 It has previously been shown that nitriles having electron withdrawing groups can form fairly reactive electrophiles in the Houben-Hoesch reaction. This has been the basis for synthetic methodologies leading to halogen-substituted ketones, 2 aminoketones, 3 N -heterocyclic ketones, 3 and other products. 4 Likewise, Shudo and Ohwada have described a superacid-promoted Houben-Hoesch reaction in which dicationic species are formed and these superelectrophilic conversions are shown give good yields aryl ketones.…”
Section: Introductionmentioning
confidence: 99%
“…Several other photochemical trifluoromethylations by trifluoroiodomethane were reported. From the tricyclic pyr-role 8, the regioisomeric substitution products 9 and 10 were formed, 10 and from the substituted pyrroles 11 and 13 the 2-trifluoromethylpyrroles 12 11 and 14 12 were prepared in moderate and good yields, respectively (Scheme 3).…”
Section: Methodsmentioning
confidence: 99%
“…Hz, 2 ), 1.7-1.6 (m, 2 ), 1.42-1.3 (m, 2 ), 0.9 (t, J = 7 Hz, Methyl l-[4-[[2-n-Butyl-4-(hydroxymethyl)-5-chloroimidazolyl]methyl]phenyl]-lH-pyrrole-2-carboxylate (20). Elution with ethyl acetate of the reaction mixture that afforded 18 provided the isomer methyl 1-[4-[ [2-n-butyl-4-(hydroxymethyl)-5-chloroimidazolyl] methyl]phenyl]-lff-pyrrole-2-carboxylate: NMR (CDCI3) 7.35 (d, J = 6 Hz, 2 ), 7.1 (m, 3 H), 6.9 (d, J = 2.5 Hz, 1 H), 6.25 (t, J = 3 Hz, 1H), 5.2 (s, 2 H), 4.65 (s, 2 H), 3.75 (s, 3 H), 2.8 (t,«7 = 7 Hz, 2 ), 1.8-1.65 (m, 2 ), 1.43-1.3 (m, 2H),0.9 (t,</=7Hz, 3H).…”
Section: Methodsmentioning
confidence: 99%